Characterisation and modelling of drying kinetics of thin ash and oak wood lamellas dried with infrared radiation and hot air : Karakterizacija i modeliranje kinetike sušenja tankih lamela drva jasena i hrasta infracrvenim zračenjem i vrućim zrakom - Straže, Aleš (Array, 2020)
Infrared and hot air drying characteristics of thin ash (Fraxinus excelsior L.) and oak (Quercus robur L.) wood lamellas were experimentally determined using an infrared and hot air laboratory device. Drying curves of 2 mm thick lamellas were established in the temperature range between 60 °C and 90 °C, and fitted by Fick’s diffusion model. Drying efficiency, drying rate and effective diffusivity have been estimated and compared between the used drying techniques. Moisture ratio exponentially decayed with duration of the process at all used temperatures. Effective diffusivity was greater in ash than oak wood, and it was not significantly influenced by the drying technique. The increased bound water diffusivity with increased drying temperature that caused shortening of the drying process was confirmed in both wood species. Similar activation energy was determined with both wood species, lower when the IR drying technique was used.